A Study Of Characteristic On The Samop Core Cooling System Using Fluent CFD. (September 2019) - Lestari, D W; Suharyana; Riyatun; Hidayanti, D
Abstract: Safety study of the cooling system of the SAMOP facility has been done. The thermal-hydraulics is required to evaluate the heat removal system in order to exhibit that sufficient cooling capacity to prevent fuel solution overheating. In this study, the inlet velocities have been varied namely 0 to 0.522 cm/s and 2.090 to 4.179 cm/s. The modelling and numerical simulation had been carried out using the Computational Fluid Dynamic (CFD) employing FLUENT 6.3.26 software . The results of water velocities were 0 – 1.045 cm/s or natural convection. The simulated maximum water temperature was (39.39 ± 0.07) °C for the inlet velocities of 0 cm/s and (32.34 ± 0.85) °C for 0.104 cm/s, respectively. The maximum water temperature was located in the channel between the central tube wall and the inner annular tube wall. The average water temperature was 27.76 °C for the inlet velocities of water from 0.209 to 4.179 cm/s. It could be concluded that the SAMOP core cooling system using natural convection was capable and optimal to prevent the fuel overheating even the value of water inlet velocity of 0.209 cm/s.